Halal Industry: A Comparative Analysis of Halal Certification Mechanisms in Indonesia and Malaysia from the Perspective of Sharia Economic Law - Zaharah, Rita; bt Nik Azhar, Nik Airin Aqmar; faizal, liky; Santoso, Rudi; Satria, Indah (ASAS, 2024)
This study examines the comparative mechanisms of halal certification between Indonesia and Malaysia from the perspective of Sharia economic law. The aim of this research is to analyze the differences and similarities in the halal certification procedures applied in both countries, as well as the legal and economic implications arising from these differences. The research method utilized is a qualitative approach with a literature review technique, where secondary data is obtained from literature, regulations, and documents related to halal certification. The analysis involves examining government policies, certification bodies, and the role of Sharia economic law in promoting the implementation of halal standards. The findings reveal that both countries have a strong Sharia legal foundation for halal certification, yet there are significant differences in implementation and standards. In Indonesia, halal certification is managed by the Halal Product Assurance Agency (BPJPH) with oversight from the Indonesian Ulema Council (MUI). In contrast, Malaysia's halal certification is handled by the Department of Islamic Development Malaysia (JAKIM), which possesses full authority and employs a more centralized and integrated approach. The economic implications of these differences include variations in certification costs, processing times, and consumer trust in halal labels. Based on the perspective of Islamic economic law, this study finds that halal certification is not merely an administrative process but a component of implementing sharia principles in the economy, including: the Principle of Justice, Social Responsibility, Consumer Protection, and Market Integrity.Keywords: Halal certification, Indonesia, Malaysia, Sharia economic law, halal industry